Laughter out of place : race, class, violence, and sexuality in a Rio shantytown - Goldstein, Donna M. (California series in public anthropology., 2013)
Donna M. Goldstein presents a hard-hitting critique of urban poverty and violence and challenges much of what we think we know about the ""culture of poverty"" in this compelling read. Drawing on more than a decade of experience in Brazil, Goldstein provides an intimate portrait of everyday life among the women of the favelas, or urban shantytowns in Rio de Janeiro, who cope with unbearable suffering, violence and social abandonment. The book offers a clear-eyed view of socially conditioned misery while focusing on the creative responses-absurdist and black humor-that people generate amid dai